Preparation of Fe3+-Deposited ZnS and its Photocatalytic Oxidation of Antibiotics Pollution - Zhang, Xiaojie; Yan, Yongsheng; Huo, Pengwei; Lu, Ziyang (Asian Journal of Chemistry, 2012)
The purpose of this paper is to prepare Fe3+-deposited ZnS and enhance the photocatalytic activity of ZnS under visible light irradiation. It is very significative to degrade ciprofloxacin using prepared photocatalyst by visible light irradiation. The bulk ZnS was synthesized by a simple hydrothermal method using Zn(CH3COO)2 and (NH2)2CS as main original reactant and poly(vinyl pyrrolidone) (PVP) (M = 10000) as the surfactant. The irradiation experiments were carried out in a photoreactor using two 150-W tungsten halogen lamps. The concentration of ciprofloxacin was determined spectrophotometrically. The efficiency of photocatalytic degradation of ciprofloxacin was affected by the amount of Fe3+ ions on the surface of ZnS, irradiation time and the dosage of photocatalyst. The kinetics data were fit Langmuir-Hinshelwood kinetic expression. The proposed mechanism could explain the processes of photocatalytic degradation of ciprofloxacin, as fluoroquinolones pollution, could be degraded using Fe3+-deposited ZnS as photocatalyst under visible irradiation. The prepared catalysts were characterized by SEM, XRD and diffusive reflectance spectra. Photodegradation of ciprofloxacin follows the first-order kinetics and the degradation rate is 0.042 min-1 at 20 mg L-1 initial concentration of ciprofloxacin.